Oil spill emergency preparedness in the Russian Arctic: a study of the Murmansk region - Maria Ivanova (Polar Research, 2011)
The issue of oil spill emergency response in north-west Russia has become increasingly important following a substantial increase in maritime transport and major offshore developments in Russian waters. This study is an initial effort to outline the public and private agencies and organizations involved in handling oil spills in the Murmansk region and the structure of the oil spill emergency response system in the region. This study examines the formal relationships between federal and regional authorities and between the different subsystems at the regional level. Due to the paucity of academic literature and public documentation on this topic, this study to a large extent bases itself on interview data. A main finding is that the regional oil spill response system has not been fully developed. It further concludes that the system lacks a clearly formulated state policy, a single governing authority and a unified structure. Finally, the study demonstrates that the agencies and organizations involved in tackling oil spill emergencies in the Murmansk region are hampered by insufficient funding, which probably reduces their preparedness to combat oil spills.